Life cycle and emergy based design of energy systems in developing countries: Centralized and localized options - KURŞUN, BERRİN (ELSEVIER, 2015)
This study analyzes the environmental performance of two centralized clean coal technologies and localized biogas digester, biomass gasifier and a solar PV by joint use of life cycle assessment (LCA) and emergy analysis. We also calculate cost of electricity generation by each of these technologies. The resulting information is utilized to determine the optimum energy mix to meet the energy demand in Rampura Village, Uttar Pradesh, India by solving a linear programming (LP) problem. The LP problem is processed in two steps: first, it is solved for four scenarios involving different practical situations and constraints. After determining the suitable scenario, the optimum energy combination within this scenario is found. The scenario and energy combination analyses reveal that performing 70% of cooking by biogas cook stoves, 30% by improved biomass cook stoves in the traditional way, and converting rest of biogas to electricity to meet irrigation and lighting energy needs is the most environmentally benign, economically feasible and socially attractive option for the village. Direct utilization of biogas for cooking makes it possible to meet all the energy demand in Rampura with local resources. Importing energy from erratic and unreliable government grid is not needed, hence energy security and reliability are ensured. Additionally, the GHG and other emissions related to cooking with inefficient stoves are also significantly mitigated (88%) through the use of biogas and improved biomass cook stoves. Energy projection through 2031 to determine changing energy patterns in the project site shows that there will be enough biogas for cooking needs in Rampura until 2031. However, by 2016, the total energy demand (cooking + irrigation + lighting) will exceed what can be met with only biogas. Then either biogas potential will need to increase or electricity will have to come from biomass or solar resources. If these local sources of energy are not enough, importing energy from centralized energy options will be necessary. Thus, increasing energy demand in developing countries will necessitate utilization of centralized energy options even in rural areas. Utilizing centralized clean coal technologies to meet this demand could ease energy related environmental problems. Alternatively, if rural development can take place without rampant consumerism and energy-intensive lifestyles, then satisfying local needs with local resources with minimum environmental impact is much more likely. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Energy technologies; Developing countries; Renewable energy; Clean coal; Life cycle assessment; Emergy; ELECTRICITY-GENERATION; CLIMATE-CHANGE; POWER; ADOPTION; FINLAND; LCA